2015
DOI: 10.3791/52159
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Leukocyte Antigen Biomarkers in Breast Cancer Utilizing Label-free Biosensor Technology

Abstract: According to the American Cancer Society, more than 200,000 women will be diagnosed with invasive breast cancer each year and approximately 40,000 will die from the disease. The human leukocyte antigen (HLA) class I samples peptides derived from proteasomal degradation of cellular proteins and presents these fragments on the cell surface for interrogation by circulating cytotoxic T lymphocytes (CTL). Generation of T-cell receptor mimic (TCRm) monoclonal antibodies (mAbs) which recognize breast cancer specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This led to the investigation of peptides eluted from soluble HLA (sHLA) complexes, recovered from the blood of patients with hematological malignancies, such as multiple myeloma, acute lymphoblastic leukemia or acute myeloid leukemia [21]. Furthermore, soluble HLA molecules complexed with disease-associated epitopes found in the blood of breast cancer patients were proposed to serve as possible biomarkers and companion diagnostics [22].…”
Section: Introductionmentioning
confidence: 99%
“…This led to the investigation of peptides eluted from soluble HLA (sHLA) complexes, recovered from the blood of patients with hematological malignancies, such as multiple myeloma, acute lymphoblastic leukemia or acute myeloid leukemia [21]. Furthermore, soluble HLA molecules complexed with disease-associated epitopes found in the blood of breast cancer patients were proposed to serve as possible biomarkers and companion diagnostics [22].…”
Section: Introductionmentioning
confidence: 99%
“…The above-mentioned study by Bassani-Stenberg ( 33 ) identified a number of peptides derived from cancer-testis antigens (CTA) and tumor-associated antigens (TAA) in the blood of patients with hematological malignancies. More recent studies observed that sHLA complexes containing peptides derived from validated CTAs (macrophage inhibitory factor ( 49 , 50 ) & NY-ESO-1 ( 51 )) can be detected in the blood of breast cancer patients ( 52 ).…”
Section: Sourcing Biomarkers From Soluble Hla: Current Evidence and E...mentioning
confidence: 99%
“…[4][5][6][7] Recent years, optical detection methods based on the effect of guided-mode resonance are often used in biological testing. For example, optical devices combined with micro-nano structures based on this theory have been used in cancer detection, 8,9 serum concentrations of human IgE antibodies detection, 10 and live cell adhesion imaging.…”
Section: Introductionmentioning
confidence: 99%